Paeoniflorin alleviates inflammatory response in IBS-D mouse model via downregulation of the NLRP3 inflammasome pathway with involvement of miR-29a. Issue 12 (December 2022) - Ke, Wei; Wang, Yongfu; Huang, Siyu; Liu, Shan; Zhu, He; Xie, Xiangyu; Yang, Huifei; Lu, Qin; Gan, Jianfeng; He, Guodong; Che, Fei; Wan, Xin; et al.
Abstract: Paeoniflorin has been traditionally used to treat pain and immunologic derangement in China. However, its detailed mechanism remains to be illuminated. We investigated the mechanism by which paeoniflorin alleviates the inflammatory response in a mouse model of irritable bowel syndrome with predominant diarrhea (IBS-D). C57BL/6 wild type (WT) and miR-29a knockout (KO) mice were randomly divided into control, model, rifaximin, and paeoniflorin groups (n = 7). IBS-D model was induced by single intracolonic instillation of 0.1 mL trinitro-benzene-sulfonic acid (TNBS, 50 mg/mL) combined with restraint stress for seven consecutive days. The treatment groups received rifaximin (100 mg/kg) and paeoniflorin (50 mg/kg) via intragastric administration for seven days, respectively. The results showed that the fecal water content, fecal pellet output, visceral sensitivity, and histopathological score after paeoniflorin treatment were lower than those of the model group in both WT and miR-29a KO mice (P < 0.05). In both lineage mice, damage was observed in the colon tissues of model group, while paeoniflorin treatment partially ameliorated the tissue damage. Serum levels of DAO, DLA, IL-1β, IL-18, TNF-α, and MPO were decreased after paeoniflorin treatment (P < 0.05), with miR-29a KO mice in a lower level compared with that of WT mice. RT-PCR showed that the relative expression of miR-29a, NF-κB (p65), NLRP3, ASC, caspase-1, IL-1β, and TNF-α was downregulated while NKRF was upregulated after paeoniflorin treatment (P < 0.05). Immunohistochemistry showed that intestinal epithelial protein levels of NLRP3, ASC, and caspase-1 decreased while those of Claudin-1 and ZO-1 increased in the paeoniflorin treatment group (P < 0.05). In general, compared with WT mice, NLRP3 inflammasome pathway targets was in much lower expression level than miR-29a KO mice. In conclusion, paeoniflorin could inhibit abnormal activation of the NLRP3 inflammasome pathway by inhibiting miR-29a in IBS-D, thereby relieving the inflammatory response of the intestinal mucosa and reconstructing the intestinal epithelial barrier. Graphical abstract: Image 1 Highlights: Paeoniflorin alleviated inflammatory response in IBS-D by downregulating miR-29a expression. Paeoniflorin inhibited the abnormal activation of the NLRP3 inflammasome pathway. After paeoniflorin treatment, damaged intestinal epithelial barrier was restored. Abstract : Paeoniflorin; IBS; miR-29a, NLRP3 inflammasome.